Can smart rural construction improve agricultural products supply chain resilience? Empirical evidence from 31 provinces in China - Wang, Hongzhi; Zheng, Jiaojiao; Ran, Haojie (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe stable and secure supply of food and important agricultural products is related to the foundation of people’s livelihoods and is a top priority for the country’s economy. The construction of a robust supply chain system for agricultural products can help to effectively cope with the impact of international political conflicts, natural disasters, emergencies, and other uncertainties. Currently, problems of chain breakage and blockage in the agricultural products supply chain occur frequently, affecting food security. It has become a pressing task to improve the resilience of the agricultural products supply chain by utilizing smart technology and other emerging forms.MethodsBased on panel data from 31 Chinese provinces (2013–2022), this study employs a two-way fixed effects model and a panel threshold model to analyze the impact mechanism of smart rural construction on the resilience of the agricultural products supply chain. Composite indices for smart rural construction and the resilience of the agricultural products supply chain were constructed using the entropy weight method. The robustness of these indices was rigorously tested through sensitivity analyses and by recalculating the smart rural construction index using the coefficient of variation method.Results and discussionUltimately, the results of the study show that smart rural construction can enhance the resilience of the agricultural products supply chain and improve it by promoting the upgrading of industrial structure. The effect of smart rural construction on the resilience of the agricultural products supply chain is regionally heterogeneous, with a more significant positive effect in the central and western regions. Additionally, there is a threshold effect associated with the impact of smart rural construction on the resilience of the agricultural products supply chain. The conclusions of this paper show that the smart rural construction gives new momentum for improving agricultural products supply chain resilience in China and provides theoretical and practical guidance for the modernization of China’s agriculture and rural areas, as well as the construction of a strong agricultural products country.